Analisis Faktor-Faktor Yang Mempengaruhi Akuntabilitas Kinerja Instansi Pemerintah Pada Badan Pengelolaan Keuangan Dan Asset Daerah (BPKAD) Provinsi Papua - Permana, Insan; Ratang, Westim; Rofingatun, Siti (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2024)
The aim of this research is to analyze the factors that influence the accountability of government agency performance at the Regional Financial and Asset Management Agency (BPKAD) of Papua Province. This research is a type of quantitative research with the population used being employees at the Regional Financial and Asset Management Agency (BPKAD) of Papua Province, totaling 187 employees. Based on the calculation of the sampling technique using the Slovin formula, the number of samples determined was 65 employees. The method used in this research is multiple regression analysis. Where this analysis method is a statistical method used to test the relationship between several independent variables and one dependent variable. The results of the analysis show that, the information system, internal control system and clarity of budget targets simultaneously influence the accountability of the performance of regional government agencies in the Regional Financial and Asset Management Agency (BPKAD) of Papua Province. The information system, internal control system and clarity of budget targets partially influence the accountability of the performance of regional government agencies at the Regional Financial and Asset Management Agency (BPKAD) of Papua Province. Clarity of budget targets has a dominant influence on the accountability of the performance of regional government agencies at the Regional Financial and Asset Management Agency (BPKAD) of Papua Province.